Effect of Storage Materials and Duration on Quality of Rice Seed - Bista, Mamata; Ghimire, Prakash; Khanal, Dipak; Khatri, Narayan; Marasini, Sima (Agronomy Journal of Nepal, 2022)
Storage loss of rice seed in terms of quality parameters is higher in Nepal due to lack of information about the effect of storage materials. Laboratory experiment was conducted to evaluate the effect of storage materials and storage period on quality parameters of rice seed (Oryza sativa L. cv., Bahuguni dhan-1). Rice seed was stored in seven storage materials (metal bin, plastic bin, super grain bag, PICS bag, plastic bag with jute sack, jute sack and earthen pot) in Completely Randomized Design with three replications at the Seed Laboratory of National Wheat Research Program, Bhairahawa, Rupandehi, Nepal from March to July, 2021. Seed moisture content and germination percentage were recorded before storage and after one, three and five months of storage. The population of two insect pests rice weevil and maize weevil was recorded after five months of storage. The result revealed that all the seed quality parameters under study were significantly influenced by storage materials. PICS bag followed by super grain bag was found to be superior in terms of seed moisture content, germination percentage and seed health throughout the storage period. Seed in the indigenous storage materials (earthen pot and jute sack) lost their quality significantly throughout the storage period. Future research strategies should focus on seed quality study under several indigenous storage materials found in Rupandehi district of Nepal.